Human Resource Management System (HRMS) / Bong Mee Mee - Bong , Mee Mee (2001)
HRMS (Human Resource Management System) is an interactive, web-based application developed using ASP (Active Server Pages). lt is designed to meet the need of accessing human resource information electronically by the employees of an organization. This system can be reach through network, only by authorized users. In this system, there are six modules that manage the human resource system, which are Staff Information/Personnel Management, Leave Management, Claims & Benefit Management, Training Courses, Notice Management and Search module. HRMS provides database processing system where users do not have to be concerned with the ways in which data are physically stored Rather, they are free to concentrute on matter important to them. The main advantage of using this system is that multiple users are allowed to simultaneously access the same system through client (the browser) at anytime and anywhere conveniently. However, as the number of clients increased the server would quickly become Personnel Management with client requests. Maintenance needs to be carried out regularly to ensure the accuracy, consistency, reliability and timeliness of the data further enhancement on Human Resource Management System is also necessary to fulfill future requirements to increase the effectiveness of the system.